Substance P augments tumor necrosis factor release in human monocyte-derived macrophages. - Lee, H R (1994)
Substance P (SP) is an undecapeptide that has the amino sequence Arg-Pro-Lys-Pro-Gin-Gln-Phe-Phe-Gly-Leu-Met-NH2 and that belongs to a family of structurally related peptides known as tachykinins, the latter are widely distributed in the central nervous system. SP is involved in the biological activities of cells in the immune system, including the induction of cytokines in immune cells. We have investigated the effects of SP on constitutive and/or lipopolysaccharide (LPS)-induced expression of tumor necrosis factor (TNF) in cultured blood monocyte-derived macrophages (MDM). Cells cultured in vitro for 14 days were treated with SP at various concentrations (10(-10) to 10(-6M) in the presence of LPS before culture supernatants were harvested. TNF bioactivity in culture supernatants was measured with L929 cell line MDM from 10 of 12 donors treated with a SP alone showed increased TNF production. SP and LPS also interacted in a synergistic fashion in upregulating TNF production in MDM from responders. The stimulatory effect of SP was inhibited by two SP antagonists, spantide ([D-Arg-1-D-Trp-7-D-Trp-7-D-Trp-9-leu-11]-SP) and CP-96,345 (a nonpeptide antagonist of the SP receptor). In addition, an anti SP polyclonal antibody blocked the SP effect on TNF production in cultured MDM, further indicating the specificity of these effects. These results demonstrate that SP is an important regulator of monokine production by human monocytes/macrophages.